Virtual Reality in Adult Patients Undergoing Neuraxial Anesthesia: A Scoping Review of Perioperative Psychological Outcomes and Patient Experience - Kimia Khonakdar; Maliheh Shirzad; Raha Bakhtiari; Arian Jahromi; Talieh Rostamian (Archives of Anesthesia and Critical Care, 2026)
Background: Patients undergoing neuraxial anesthesia remain conscious during surgery and may experience perioperative anxiety and psychological distress. Virtual reality (VR) has been proposed as a non-pharmacological strategy to improve patient experience. This scoping review aims to map current evidence on VR effects on psychological and experiential outcomes in adults undergoing neuraxial anesthesia. Methods: This scoping review was conducted in accordance with PRISMA-ScR guidelines. PubMed, Scopus, Web of Science, and Embase were searched up to November 2025. Studies investigating the use of virtual reality among adult patients receiving neuraxial anesthesia in the operating room were included. Information regarding study design, characteristics of the VR intervention, and reported outcomes was collected and summarized narratively. Results: 13 studies involving 1,127 participants were identified, including 12 randomized controlled trials and one matched retrospective cohort study. Most interventions employed immersive VR during the intraoperative period. Anxiety and stress were the outcomes most frequently assessed, and a large proportion of studies reported significant reductions in anxiety following VR use. Evidence regarding pain reduction was variable and showed limited and inconsistent benefits across studies. Patient satisfaction and comfort were generally improved, whereas findings related to sedative requirements were mixed, with several studies reporting reduced sedative use. Conclusion: VR appears to be a useful adjunct for enhancing perioperative patient experiences, especially with respect to anxiety reduction and patient satisfaction in adults undergoing neuraxial anesthesia. However, evidence concerning pain outcomes and medication use remains inconclusive, emphasizing the importance of conducting well-designed studies with standardized outcome measures